2017
DOI: 10.3390/w9050356
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Molluscan Fauna as Model Taxon for the Ecological Classification of River Estuaries

Abstract: River estuaries are important aquatic environments characterized by large environmental gradients in their water quality, riverbed material, and microtopography in the longitudinal and transverse directions. The geography or habitats in river estuaries differ depending on the energy from the tide, waves, and river; therefore, the biota inhabiting river estuaries vary depending on the river estuary type. In view of this, for effective conservation in river estuaries, there is a need for information about potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The presence of Cerithidea cingulata in the ponds indicates the effect of mangrove development on the environment. The species C. cingulata is adapted to habitats with a large tidal range, abundant silt and vegetation (Itsukushima et al 2017). Cerithidea is known to be a mangrove-associated benthic species (Zvonareva et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Cerithidea cingulata in the ponds indicates the effect of mangrove development on the environment. The species C. cingulata is adapted to habitats with a large tidal range, abundant silt and vegetation (Itsukushima et al 2017). Cerithidea is known to be a mangrove-associated benthic species (Zvonareva et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In total, 14 environmental characteristics were used in this study. Previous studies found that these factors affect species richness and distribution in temperate estuaries, including tidal rivers (Inui et al, 2016; Itsukushima et al, 2017, 2019; Nicolas et al, 2010). In the present study, estuarine environmental characteristics refer to factors measured at or in river mouths, and basin environmental characteristics refer to factors measured within river systems.…”
Section: Methodsmentioning
confidence: 95%
“…The environmental characteristics of the Kyushu region are diverse because the island is surrounded by the Sea of Japan, the Pacific Ocean, and the East China Sea (Fujikura et al, 2010). As a result, various benthic communities adapted to an estuarine environment occur (Itsukushima et al, 2017; Itsukushima, Yoshikawa, & Morita, 2019). Although these estuarine environments have been devastated in central Japan, such as Tokyo Bay, as a result of anthropogenic impacts (Yuhara & Furota, 2014), natural environments remain in the Kyushu region (Henmi et al, 2014, 2017), which is an important conservation area for estuarine ecosystems in Japan.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations